2021
DOI: 10.1177/10596011211011296
|View full text |Cite
|
Sign up to set email alerts
|

From Job Resources to Idea Implementation: A Moderated Sequential Mediation Model

Abstract: Considering the motivational path of the Job Demands-Resources (JD-R) model, this study investigates a multistep process by which contextual job resources might have an indirect effect on idea implementation. Among 187 shop floor employees of a manufacturing company, we found support for a model whereby job control has an indirect effect, over a 5-month time frame, on idea implementation through employee work engagement and personal initiative. In addition, we found that the indirect effect of job control on i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 67 publications
1
3
0
Order By: Relevance
“…These three components were identified as crucial determinants for the successful completion of implementation activities. Our findings concerning these three components align with established conceptualizations that emphasize the dependence of idea implementation on organizational resources and support (Skerlavaj et al, 2014; Weigt‐Rohrbeck & Linneberg, 2019), individuals' capability to implement innovations (Birdi et al, 2016; Karlsson & Skålén, 2015) and their active involvement in the implementation process (Audretsch et al, 2021; Goepel et al, 2012; Massei et al, 2022). In this section, we discuss we discuss the identified determinants together with the specific individual‐level factors that our review revealed as the most distinctive and impactful for the successful implementation of ideas.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…These three components were identified as crucial determinants for the successful completion of implementation activities. Our findings concerning these three components align with established conceptualizations that emphasize the dependence of idea implementation on organizational resources and support (Skerlavaj et al, 2014; Weigt‐Rohrbeck & Linneberg, 2019), individuals' capability to implement innovations (Birdi et al, 2016; Karlsson & Skålén, 2015) and their active involvement in the implementation process (Audretsch et al, 2021; Goepel et al, 2012; Massei et al, 2022). In this section, we discuss we discuss the identified determinants together with the specific individual‐level factors that our review revealed as the most distinctive and impactful for the successful implementation of ideas.…”
Section: Discussionsupporting
confidence: 83%
“…Personal initiative involves taking an active and self‐starting approach to work and going beyond formal job requirements (Speier & Frese, 1997). Individuals with high personal initiative are more efficient in the idea implementation stage (Audretsch et al, 2021; Goepel et al, 2012; Massei et al, 2022), as they have a higher motivation to realize ideas and are thus able to reach higher levels of innovation performance (Miron et al, 2004). Personal initiative is particularly desirable in ambiguous innovation settings or when organizational culture does not support innovation (Weigt‐Rohrbeck & Linneberg, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations